The Implication of Sustainable Career Development Implementation (PKB) On Teachers’ Career Management in an Education Unit - Nurhayati, Yuli (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aims to examine the implications of the implementation of the Pengembanagan Keprofesian Berkelanjutan (PKB) policy on teacher career management in junior high schools in Bandung.  The implication is seen in Penilaian Kinerja Guru  (PKG) planning where the teacher explores her career needs, in the implementation of PKB where the teacher tries her career strategy, and in the evaluation where the teacher reflects on PKB. Teacher career management appears in the aspects of planning, implementation, and evaluation of  PKB